Nucleoside cyclic 3',5'-phosphorothioates with purine and pyrimidine scaffolds. A chemical minireview - Kjell Undheim (Elsevier, 2022)
The common nucleobases purine (adenine and guanine) and pyrimidine (cytosine, uracil and thymine) in naturally occurring nucleosides and their 3',5'-cyclic phosphates are β-bonded to the anomeric carbon (C1') of d-ribose or its 2'-deoxy congener. These compounds are important second messengers and regulate a broad range of essential cellular functions in response to various hormones. The structural basis for this review is phosphorothioates (cNMPS) of cyclic 3',5'-nucleosides where one of the oxygen atoms pendant from the phosphorus atom in cNMP has been replaced by a sulfur atom for the purpose of modifying physicochemical properties in a positive manner for improved bioefficacy. The nucleoside scaffold can be modified at the sugar moiety or at the hetaryl base, or by the configuration of the glycosidic bond. Modifications at the nucleobase have primarily been focused on inserting substituents into the heterocyclic structure, removing or adding annular hetero atoms, or changing the relative positions of the annular atoms. Substituent manipulations can be effected prior to, or after the construction of the 3',5'-cyclophosphorothioate scaffold. The naturally occurring scaffold can serve as a substrate for structural modifications of peripheral substituents by nucleophilic substitution reactions and metal-catalyzed carbylations. Stereoselectivity is generally low in cyclothiophosphorylation of nucleosides with phosphorus halides or activated esters. A variety of riboside analogues from antiviral investigations can be included as substrates in this work. P(III) esters or halides react in a similar manner to form cyclic phosphites that are oxidatively thiated. In another process, a cyclic nucleotide is aminated under high sterical control to afford an amidate from a primary amine. A subsequent thiation of the amidate using carbon disulfide under basic conditions delivers 3',5'-cyclic phosphorothioates with retention of the true configuration at the phosphorus atom. These types of changes have served to create new groups of cyclic nucleotide analogues.